2023
DOI: 10.1021/acs.nanolett.2c04850
|View full text |Cite
|
Sign up to set email alerts
|

All-Optical Reconfigurable Excitonic Charge States in Monolayer MoS2

Abstract: Excitons are quasi-particles composed of electron–hole pairs through Coulomb interaction. Due to the atomic-thin thickness, they are tightly bound in monolayer transition metal dichalcogenides (TMDs) and dominate their optical properties. The capability to manipulate the excitonic behavior can significantly influence the photon emission or carrier transport performance of TMD-based devices. However, on-demand and region-selective manipulation of the excitonic states in a reversible manner remains challenging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…from the surrounding environment can also provide excessive charges, leading to ∼10 times decrease of the recombination rate of excitons in monolayer MoS 2 . 141 Regarding this problem, Huang et al 81 used a fs laser to reversibly switch the excitons in monolayer MoS 2 between the Via the modulation of exciton state, the laser can indirectly influence other physical properties of 2D materials, for example, the electroabsorption and magnetism modulation. 142,143 Recently, Xu et al reported the tuning of spin−spin interactions between moire-trapped carriers through optical excitation, which yielded ferromagnetic order in WS 2 /WSe 2 moireś uperlattices.…”
Section: Laser-assisted Defect and Excitonmentioning
confidence: 99%
See 2 more Smart Citations
“…from the surrounding environment can also provide excessive charges, leading to ∼10 times decrease of the recombination rate of excitons in monolayer MoS 2 . 141 Regarding this problem, Huang et al 81 used a fs laser to reversibly switch the excitons in monolayer MoS 2 between the Via the modulation of exciton state, the laser can indirectly influence other physical properties of 2D materials, for example, the electroabsorption and magnetism modulation. 142,143 Recently, Xu et al reported the tuning of spin−spin interactions between moire-trapped carriers through optical excitation, which yielded ferromagnetic order in WS 2 /WSe 2 moireś uperlattices.…”
Section: Laser-assisted Defect and Excitonmentioning
confidence: 99%
“…from the surrounding environment can also provide excessive charges, leading to ∼10 times decrease of the recombination rate of excitons in monolayer MoS 2 . Regarding this problem, Huang et al used a fs laser to reversibly switch the excitons in monolayer MoS 2 between the neutral and charged states in an ambient environment. Figure (c) summarizes the PL evolution the MoS 2 monolayer under fs laser irradiation.…”
Section: Optical Tuning Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional (2D) semiconductors, such as transition metal dichalcogenides (TMDs) with the chemical formula MX 2 (where M = Mo, W, Ru, ... and X = S, Se, Te, ...), 1,2 have emerged as promising nanomaterials for next-generation chipscale optoelectronic devices due to their fascinating properties such as indirect-to-direct bandgap transition, 1 strong Coulomb interaction, 3 and valley-specific circular dichroism. 4 Since the bandgaps of monolayer TMDs (1L-TMDs) are sensitive to the dielectric environment, 5,6 mechanical strain, 7 and external perturbation, 8 such 2D semiconductors provide ideal platforms for manipulating light−matter interaction at the nanoscale, which has spawned many applications such as solar cells, 9 light-emitting devices, 10 and photodetectors. 11 Nowadays, the industrial production of 2D semiconductors is becoming possible with the development of large-scale production techniques such as chemical vapor deposition (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the phenomenon of exciton-to-trion conversion in 2D semiconductors has attracted significant attention. Trions offer distinct advantages over neutral excitons for optoelectronic device applications. Trions are responsive to external bias, enabling electrical control over their spatial distribution, a feature that can be harnessed in the development of trion-based integrated circuits. Additionally, trions have relatively shorter lifetimes and lower binding energies compared to excitons, making them conducive to the development of highly efficient photovoltaics, such as trion-based photocurrent devices and solar cells. To enhance the rate of exciton-to-trion conversion and improve the performance of trionic devices, plasmonic nanostructures are considered an ideal platform. ,, Plasmonic structures can induce hot electron generation, facilitate electron funneling, and reduce trion lifetimes, thus enhancing the functionality, selectivity, and sensitivity of such devices. ,, …”
mentioning
confidence: 99%